ESTUDO DA ESTRUTURA CRISTALINA DE PIGMENTOS DE ZIRCONITAS A PARTIR DOS SISTEMAS ZrSiO4-Co3O4 E ZrSiO4-Cr2O3 UTILIZANDO O MÉTODO DE RIETVELD - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
Samples of zircon (ZrSiO4) not doped and doped with 1, 5 , 10 and 20 in mass of cobalt and chrome, they were prepared from the conventional ceramic method. The powder obtained was analyzed by X-Ray diffraction, with the aim of analyzing the structure, identifying the formed phases, quantifying these phases and suggesting a possible doping site occupation. Rietveld method of crystalline structures refinement was used in the structural analysis of the phases, the refinement software used was Rietan-2000. In the samples doped with cobalt there was a formation of three new phases: Co2SiO4 cubic, Co2SiO4 trigonal and ZrO2 monoclinic, besides the primary phases ZrSiO4 tetragonal and Co3O4 cubic, while in the not doped sample we could only see the ZrSiO4 tetragonal phase, and in the samples doped with chrome didn´t occur the formation of new phases besides the primaries ZrSiO4 tetragonal and Cr2O3 hexagonal. It was verify, then, that the cobalt doped with 1 collaborated to the appearing of Co2SiO4 cubic phase, the Co2SiO4 cubic, Co2SiO4 trigonal phases appeared with 5, with 10 there were the tree new phases: Co2SiO4 cubic, Co2SiO4 trigonal and ZrO2 monoclinic, there weren´t new phases with 20 % there was only the affirmation of the identified phases. The powder produced was the blue shade. The quantitative phases analysis revealed that the increasing of the Co2SiO4 cubic, Co2SiO4 trigonal and ZrO2 monoclinic phases causes decreasing of the ZrSiO4 tetragonal phase. But the chrome dope didn´t help in the appearing of new phases in any of the concentrations studied. The powder obtained was of green shade. The volume analysis of the unitary cell, distance, angle and quantitative don´t allow us to conclude that a substitution is happening, but the results suggest that until about 5 of cobalt a substitution occurs in the silicon site, it looks like that over this quantify it also begins to happen a substitution in the zirconium site. Yet the chrome don´t seem to interact so that can cause substitution in the crystal structure, only remaining mixtured in the zirconite solid solution. The refinement indicators made with all the samples indicate the good quality of the obtained results.
Keywords: difração de raios X; Rietveld; Rietan-2000 e zirconita; X-Ray diffraction; Rietveld Method; Zirconite; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA